Pleiotropic Effects of a KCNQ1 Variant on Lipid Profiles and Type 2 Diabetes: A Family-Based Study in China - Xiaowen Wang; Junhui Wu; Yao Wu; Mengying Wang; Zijing Wang; Tao Wu; Dafang Chen; Xun Tang; Xueying Qin; Yiqun Wu; Yonghua Hu (Journal of Diabetes Research)
Objective. The genetic variant rs2237895, located in the Potassium Voltage-Gated Channel Subfamily Q Member 1 (KCNQ1) gene, has been replicated to be associated with type 2 diabetes mellitus (T2DM) susceptibility, but the relationship with lipids is conflicting. Furthermore, the common genetic predisposition to T2DM and lipids was not fully detected. Methods. In total, 5839 individuals (2220 were T2DM patients) across 2885 families were included. The effect of rs2237895 on T2DM and lipids was estimated using linear regression and logistic regression models after adjustment for multiple covariates. Mediation analysis was then used to test whether KCNQ1 participated in T2DM pathogenesis via lipid-mediated pathways. Results. Per allele-C of rs2237895 was associated with 17% (11-23%, P<0.001) increased T2DM risk. Moreover, it was correlated with 5% (1-9%, P=0.019), 4% (1-7%, P=0.019), 2% (0-3%, P=0.045), and 2% (0-3%, P=0.009) higher total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), apolipoprotein A, and apolipoprotein B (Apo-B) concentrations, respectively. Nevertheless, the genetic susceptibility for higher T2DM risk was correlated with higher high-density lipoprotein cholesterol (HDL-C) level (2%, 0-3%, P=0.026). Mediation analysis showed only TC, LDL-C, and Apo-B had small significant mediated effects, with 2.9%, 2.3%, and 3.1% of the total effects of rs2237895 on T2DM being mediated by them, respectively. Conclusion. KCNQ1 had pleiotropic effects on lipids and T2DM, and the unexpected genetic effect on association of HDL-C with T2DM was observed, indicating the different pathways to lipids and T2DM. Further research studies are needed to verify potential biological mechanisms.